Preparação e caracterização do catalisador óxido misto de cobre-zinco-alumínio, obtido via complexação (processo citrato), para a transformação do etanol a acetato de etila - Reis, Rubem da Cunha (1991)
Cu-Zn-Al mixture oxides catalysts with atomic ratios r-Cu/Zn=3,0 and R=Cu+Zn/Al=1,2 were obtained by means of citric complexing method. The influence of citric acid content was studied varying P=(eq.citric acid/Eq.metal) between 0,7-1,5 and the calcination temperature from 400 to 700°C in the precursors. Precursors and oxides were characterized by IR, TDA, TGA, XRD, SBET, TPR, SCU and SEM. The thermal decomposition of the precursors was studied in N2 and air atmosphere. The X-rays diphratograms of the calcinated oxides presented two cristallite phases: CuO and ZnAl2 04. The TPR curves showed an increment of CuO phase segregation as the calcination temperature was increased. The catalytic activity of this system was checked through the direct transformation of ethanol varying contact tim e and reaction temperature. It was verified that the catalysts presented decreasing activity for ethyl acetate when Cuo segregation increased.